2020
DOI: 10.3389/fcell.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of HSP70 in Spinal Neurons Alleviates Opioids-Induced Hyperalgesia via the Suppression of Endoplasmic Reticulum Stress in Rodents

Abstract: A major unresolved issue in treating pain is the paradoxical hyperalgesia produced by the gold-standard analgesic morphine and other opioids. Endoplasmic reticulum (ER) stress has been shown to contribute to neuropathic or inflammatory pain, but its roles in opioids-induced hyperalgesia (OIH) are elusive. Here, we provide the first direct evidence that ER stress is a significant driver of OIH. GRP78, the ER stress marker, is markedly upregulated in neurons in the spinal cord after chronic morphine treatment. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Hua et al [ 57 ] administered mesenchymal stem cells (MSC) either 1 day before, 7 days before, or 14 days after morphine administration. Lin et al [ 58 ] administered heat shock protein 70 (HSP70) using an adenovirus 24 h before, 24 h after, and 72 h after the first morphine injection during a twice a day morphine injection regimen that lasted 6 days. The trial lengths of morphine trials were very variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hua et al [ 57 ] administered mesenchymal stem cells (MSC) either 1 day before, 7 days before, or 14 days after morphine administration. Lin et al [ 58 ] administered heat shock protein 70 (HSP70) using an adenovirus 24 h before, 24 h after, and 72 h after the first morphine injection during a twice a day morphine injection regimen that lasted 6 days. The trial lengths of morphine trials were very variable.…”
Section: Resultsmentioning
confidence: 99%
“…Only four combination interventions were investigated: ketamine and gabapentin, hydrogen-rich saline and Ro 25-6981, PHA-543613 and PNU-120596, and ketamine and KN93. Furthermore, only 17 trials investigated more than one intervention, and only Doyle et al [ 27 ] and Lin et al [ 58 ] investigated more than three interventions. These 17 trials can provide direct comparisons of interventions, although some of the trials slightly varied their experimental methodology between the interventions they tested.…”
Section: Discussionmentioning
confidence: 99%
“…Our RNA sequencing data showed that while this gene was expressed in both sexes, it was specifically upregulated only in males post tumor growth. Interestingly, hsp70 has been demonstrated to have a protective role in pain during nerve damage (99,100), migraine (101) and opioid-induced hyperalgesia (102).Therefore, upregulation of Hsp70 in males post-tumor growth might indicate that male neurons might express an endogenous feedback mechanism to suppress pain that may be lacking in females. In addition to the common BPs, sex-selective BPs were identified post-tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-accepted that chronic morphine administration leads to neuroinflammatory responses in the spinal cord, characterized by the release of proinflammatory cytokines [ 2 ]. In morphine-evoked neuroinflammation, N -methyl- d -aspartate receptor (NMDA-R)-mediated central hyperalgesia plays a vital role in the development of morphine tolerance [ 26 , 27 ]. It was reported that NMDA-R/nitric oxide (NO) pathway antagonists could enhance the antinociceptive effect of morphine.…”
Section: Discussionmentioning
confidence: 99%